Kyai and Japanese Military - Kobayashi Yasuko (Studia Islamika, 1997)
During the second world war in Southeast Asia, the Japanese army tried to gain the support and cooperation of the people it occupies. In this case the policy becomes very important political Islam in Indonesia, and one prominent characteristic of Japanese politics is concerned with the role of Islamic clerics. But when he landed in Indonesia, the Japanese military has not formulated political Islam is to be implemented. Then immediately stated that the Japanese military government respect the religious population.DOI: 10.15408/sdi.v4i3.772